2017
DOI: 10.1002/clen.201700096
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 and ZnO Nanoparticles Toxicity in Barley (Hordeum vulgare L.)

Abstract: In this study, the effects of TiO2 and ZnO nanoparticles (0, 5, 10, 20, 40, and 80 mg kg−1) on seed germination, root elongation, chlorophyll content, and the activities of antioxidant enzymes of barley (Hordeum vulgare L.) are studied. The number of seeds germinated and roots elongated in germinated plants (tillering stage) are determined on day 7. Seedlings are transferred to pots containing 50 g turf and grown for 21 days. Antioxidant levels (superoxide dismutase, catalase, ascorbate peroxidase, glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…The former (shortened shoot by n-TiO 2 ) is similar to that observed in Mentha piperita [46]. On the contrary, n-TiO 2 had no effect at lower concentrations of 5-20 mg/L on T. aestivum [14] or even at higher concentrations of 200-4000 mg/L on Z. mays [6].…”
Section: Effects Of N-sio 2 and N-tio 2 On Germination And Plant Growthsupporting
confidence: 77%
“…The former (shortened shoot by n-TiO 2 ) is similar to that observed in Mentha piperita [46]. On the contrary, n-TiO 2 had no effect at lower concentrations of 5-20 mg/L on T. aestivum [14] or even at higher concentrations of 200-4000 mg/L on Z. mays [6].…”
Section: Effects Of N-sio 2 and N-tio 2 On Germination And Plant Growthsupporting
confidence: 77%
“…In this study, at the concentration of 10 mg L −1 ZnO nanoparticles concentration had an inhibitory effect on bread wheat ( Triticum aestivum L. İkizce) and provocative effect on barley ( Hordeum vulgare L. Ramata). These contradictory effects on rape, ryegrass, Zea mays, maize, and wheat and barley were reported in the literature, before.…”
Section: Discussionmentioning
confidence: 81%
“…By the way, it has been reported by many researchers that the ZnO nanoparticles variously effected on seed germination, seedling vigor, root elongation on wheat. These studies indicated the positive, negative, or ineffective impacts of ZnO nanoparticles depending on nanoparticles size and concentrations . While Awasthi et al and Solanki and Laura reported the positive effects of ZnO on wheat at about 13 nm (50 mg L −1 ZnO) and 40–50 nm (250 and 500 mg L −1 ZnO) mean size, respectively, on the other hand, Bagawade and Jagtap noted that ZnO nanoparticles (3–5 nm mean size) negatively affected wheat at the concentration of 1000–2000 mg L −1 ZnO.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…When worker bees make a new queen, they choose small larvae and feed them with royal jelly. This type of feeding triggers the development of queen morphology including the fully developed ovaries needed to lay eggs (Doğaroğlu & Doğaroğlu, 2015).…”
Section: Discussionmentioning
confidence: 99%